Love songs from a shallow grave - Cotterill, Colin (Cotterill, Colin. Dr. Siri Paiboun series., 2010)
When a female security officer is discovered stabbed through the heart with a fencing sword, Dr. Siri's instincts tell him there is more to the mystery than anyone can imagine.